Antropoceno: uma análise das modificações do meio ambiente, resultante da ação do homem - estudo de caso: São Miguel/RN - Queiroz, Lucas Rego de (Universidade Federal Rural do Semi-Árido, 2019)
The man throughout his history modified the surface of the Earth in search of better living conditions, and this process began with the extraction of natural resources that served as raw material to meet all the basic needs of man, in addition to promoting Comfort and progress. Over the years the human population has grown considerably, causing the need for a greater number of resources, a greater demand for areas that can be inhabited, this implies numerous modifications, which according to some scientists They trigger the emergence of a new geological era, the Anthropocene. Based on bibliographic surveys, and also through the analysis of historical maps of the city of São Miguel-RN, the work analyzes man's actions as a surface modifier, and these actions are linked to the population's growth, confirming So the theory of I have man as the creator of a new geological era, the Anthropocene, besides showing that the actions also affect the small localities.
Keywords: Agente modificador; Evolução historica; Crescimento populacional; Historic evolution; Modifying agent; Population growth; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA